PENGARUH PENGGUNAAN APLIKASI TIK TOK TERHADAP PERILAKU ADICTED SISWA SLTA DI KOTA PEKANBARU - Nazhifah; M. Fadhil Andika Putra; Ilham Syaputra; Popi Saputra Zalukhu; Akmal Khairi (Mediakita, 2021)
This study aims to determine the effect of the short video Tik Tok application on the existence of senior high school students. The theory used in this research is the CMC (Computer Mediated Communication) theory which is applied by the media to users which causes mood modification, tolerance, withdrawal, and conflict. The research approach used a quantitative approach using the Rho Spearman correlation analysis.The data collection technique used a questionnaire. The results showed that there was a significant correlation between the use of the Tik Tok application and the existence of high school equivalent students in Pekan Baru Riau. There were 36 respondents in this study using purposive sampling technique. The coefficient value shows a correlation of 0.637 with a significance level of p = 0.000 (p <0.05), meaning that the higher the use of the Tik Tok application, the higher the existence of junior high school students. On the other hand, the lower the use of the Tik Tok application, the lower the existence of high school students. The Tik Tok application shows that it can channel the talents of its users to share hobbies, talents and expertise with everyone. The advantage of Tik Tok that other applications do not have is the completeness of various video features for its users. Although there are social media such as YouTube that offers video features in the form of video sharing channels, YouTube only provides channels for certain users who meet the requirements, not for everyone.